Special aspects of inspiration as practice of resocialization of combatants with disabilities - Кривоконь, Н. І. (Psychological Counseling and Psychotherapy, 2017)
The publication highlights the empowerment features as psychosocial practice for re-socialization of combatants with disabilities. Basic conceptual positions that characterize the emotional, cognitive and behavioral components of empowerment are presented based on the analysis and systematization of the authors’ experience in psychological support of combatants. In particular, the article describes the contents of experiences as a factor of equilibrium of emotional states of people with disabilities, defines the role of values and emphasizes the complexity of their choice for understanding the situation in life after disability, stresses the importance of the activity for the successful re-socialization of combatants with disabilities